1976
DOI: 10.1128/aem.31.1.39-45.1976
|View full text |Cite
|
Sign up to set email alerts
|

Influence of growth temperature on glucose metabolism of a psychotrophic strain of Bacillus cereus

Abstract: The influence of temperature on glucose metabolism of a psychrotrophic strain of Bacillus cereus was investigated. The pH of the growth medium and sporeforming frequencies of B. cereus varied when grown at 32, 20, or 7 C. Radiorespirometric analyses revealed that vegetative cells of B. cereus metabolized glucose by simultaneous operation of the Embden-Meyerhof-Parnas pathway and the pentose phosphate pathway. As the growth temperature decreased, glucose was metabolized with increased participation of the pento… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
9
0

Year Published

1979
1979
2016
2016

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(9 citation statements)
references
References 27 publications
0
9
0
Order By: Relevance
“…tributed to the observed δ 13 C of respired CO 2 (Dijkstra et al, 2011;Tcherkez et al, 2012). It could simply result from a proportionally increasing flux through respiratory pathways, with associated stronger expression of 13 C discrimination by the enzymes involved (Tcherkez et al, 2012), or could result from increasing temperatures altering the relative fluxes through respiratory pathways (Chung et al, 1976;Wittmann et al, 2007;Dijkstra et al, 2011) such that the overall observed respiratory 13 C discrimination increased with temperature. This may be possible given that respiratory pathways can exhibit distinct fractionation factors (Bathellier et al, 2009 and references therein) and prompt different, specific C atoms to undergo decarboxylation from the two glucose units of the substrate cellobiose, which contain non-randomly distributed 13 C atoms (Rossmann et al, 1991;Gleixner and Schmidt, 1997).…”
Section: Resultsmentioning
confidence: 99%
“…tributed to the observed δ 13 C of respired CO 2 (Dijkstra et al, 2011;Tcherkez et al, 2012). It could simply result from a proportionally increasing flux through respiratory pathways, with associated stronger expression of 13 C discrimination by the enzymes involved (Tcherkez et al, 2012), or could result from increasing temperatures altering the relative fluxes through respiratory pathways (Chung et al, 1976;Wittmann et al, 2007;Dijkstra et al, 2011) such that the overall observed respiratory 13 C discrimination increased with temperature. This may be possible given that respiratory pathways can exhibit distinct fractionation factors (Bathellier et al, 2009 and references therein) and prompt different, specific C atoms to undergo decarboxylation from the two glucose units of the substrate cellobiose, which contain non-randomly distributed 13 C atoms (Rossmann et al, 1991;Gleixner and Schmidt, 1997).…”
Section: Resultsmentioning
confidence: 99%
“…tributed to the observed δ 13 C of respired CO 2 (Dijkstra et al, 2011;Tcherkez et al, 2012). It could simply result from a proportionally increasing flux through respiratory pathways, with associated stronger expression of 13 C discrimination by the enzymes involved (Tcherkez et al, 2012), or could result from increasing temperatures altering the relative fluxes through respiratory pathways (Chung et al, 1976;Wittmann et al, 2007;Dijkstra et al, 2011) such that the overall observed respiratory 13 C discrimination increased with temperature. This may be possible given that respiratory pathways can exhibit distinct fractionation factors (Bathellier et al, 2009 and references therein) and prompt different, specific C atoms to undergo decarboxylation from the two glucose units of the substrate cellobiose, which contain non-randomly distributed 13 C atoms (Rossmann et al, 1991;Gleixner and Schmidt, 1997).…”
Section: Resultsmentioning
confidence: 99%
“…in this study were similar in design to those described by Wang (40). The methods used were modified from those of several authors (3,11,30). Cells for the radiorespirometric experiments were grown and harvested as described above.…”
Section: Radiorespirometry the Radiorespirometers Usedmentioning
confidence: 99%
“…At the termination of the experiment, the flasks were chilled and the cells were separated from the buffer medium by centrifugation. The radioactivity in the cells and medium was determined as described by Chung et al (11). The counting efficiency of 14C was approximately 90%, and quenching was corrected for by the internal standard method.…”
Section: Radiorespirometry the Radiorespirometers Usedmentioning
confidence: 99%